Fourth International Workshop on Variability Modelling of Software-intensive Systems. Proceedings - David Benavides; Don Batory; Paul Grünbacher (Universität Duisburg-Essen, Institut für Informatik und Wirtschaftsinformatik (ICB), 2010)
This ICB Research Report constitutes the Proceedings of the 4th International Workshop on Variability Modelling of Software-intensive Systems (VaMoS'10), which was held from January 27-29, 2010 at the Johannes Kepler University Linz.
Keywords: 650; Wirtschaftsinformatik